Thrombosis prevention in percutaneous coronary interventions - V. P. Lupanov; A. N. Samko (Кардиоваскулярная терапия и профилактика, 2009)
The introduction of drug-eluting stents has been a major achievement of interventional cardiology. These stents  demonstrate good clinical effectiveness and safety profile. However, prevention of restenosis and late stent thrombosis remains an important problem. The potential of antithrombotic treatment (Aspirin, clopidogrel) and postintervention management in patients with drug-eluting and non-drug-eluting stents are discussed.